HUBUNGAN PENGETAHUAN GIZI, SIKAP, DAN TEMAN SEBAYA DENGAN POLA KONSUMSI FAST FOOD PADA REMAJA DI SMAN 6 DEPOK - Cahya Wulandari Puspa Ningrum (2023)
Adolescence is a period when individuals tend to feel unstable and are easily influenced by the environment and the passage of time. One of the impacts is healthy as well as unhealthy eating patterns, such as consumption of fast food. Various factors influence fast food consumption patterns in adolescents, such as nutritional knowledge, attitudes, and peers. Nutritional knowledge can influence attitudes and behaviors toward food choices. Adolescents are vulnerable to peer influence, which may affect their fast-food consumption behaviors. The purpose of this study was to determine the relationship between nutritional knowledge, attitude, and peers with fast-food consumption patterns among adolescents at SMAN 6 Depok. This study used a cross-sectional design with a stratified random sampling technique. The sample involved 108 participants. Data was collected by filling out questionnaires. Data processed using the chi-square test. Based on the statistical tests, there is no relationship between nutritional knowledge and fast-food consumption patterns (p-value = 0.286). There is a relationship between attitude (p-value = 0.000), peers (p-value = 0.035), and fast-food consumption patterns. Increased balanced nutritious food-related knowledge as well as good attitudes and peers are needed to create an impact on healthy eating patterns.